Assessment of optimal right ventricular pacing site using invasive measurement of left ventricular systolic and diastolic function - Vancura, Vlastimil; Wichterle, Dan; Melenovsky, Vojtech; Kautzner, Josef (Europace, 2013)
AIMS: Right ventricular apical pacing has a detrimental effect on left ventricular (LV) function. More optimal pacing site may be found by invasive measurement of LV mechanical performance during pacing from different RV pacing sites. We aimed to investigate the effect of RV pacing lead location on invasive indices of LV mechanical performance. METHODS AND RESULTS: Patients undergoing catheter ablation for persistent atrial fibrillation were enrolled. Single-site endocardial pacing from the lateral LV region was periodically switched to pacing from the mapping catheter navigated to different RV sites within the three-dimensional electroanatomical RV map. SystIndex, DiastIndex, and PPIndex were defined as the ratio of LV dP/dtmax, LV dP/dtmin, and arterial pulse pressure during RV pacing to corresponding values from adjacent periods of LV pacing. Haemodynamic data were analysed in 18 RV segments created by dividing RV horizontally (basal, mid, and apical portion), vertically (inferior, mid, and superior portion) and frontally (septum and free wall). Eight patients (58 ± 7 years; 2 females; 26 ± 4 RV pacing sites per patient) were enrolled into the study. Compared with LV pacing, the best RV pacing values of SystIndex and DiastIndex were achieved in basal-mid-septal segment (+6.9%, P = 0.02 and +3.4%, P = 0.36, respectively) while the best PPIndex was obtained in superior-mid-septal segment of RV (+4.5%, P = 0.02). All indices were fairly concordant showing significant improvement of haemodynamics during RV pacing in the direction from free wall to septum, from apex to base, and from inferior to superior segments. CONCLUSION: The best LV mechanical performance was achieved by RV septal pacing in the non-apical mid-to-superior segments.
Keywords: Electroanatomical mapping; Haemodynamics of pacing; Female; Electrophysiologic Techniques, Cardiac; Heart Ventricles; systola; Atrial Fibrillation; elektrofyziologické techniky kardiologické; Diastole; ženské pohlaví; Resynchronization; srdeční komory; Catheter Ablation; Predictive Value of Tests; Optimal pacing site; prediktivní hodnota testů; časové faktory; funkce levé komory srdeční; Time Factors; lidé; katetrizační ablace; Right ventricular pacing; funkce pravé komory srdeční; Electrocardiography; krevní tlak; elektrokardiografie; Cardiac Pacing, Artificial; Ventricular Function, Right; Ventricular Septum; Male; Systole; diastola; fibrilace síní; lidé středního věku; mužské pohlaví; kardiostimulace umělá; Blood Pressure; mezikomorová přepážka; Middle Aged; Ventricular Function, Left; Humans